Legal Implication and Challenge of Using Medical Record as Evidence in the Indonesia’s Justice System - Ustani, Titik; Vitrianingsih, Yeni; Mardikaningsih, Rahayu (Metromedia, 2024)
Medical records have a strategic role as legal evidence in the justice system in Indonesia. This document had governed by various regulations, as Law Number 29 Year 2004 on Medical Practice, emphasizes the importance of maintaining the confidentiality of medical records. However, the implementation of using medical records as evidence faces various challenges if medical personnel haven’t legal understanding and the lack of adequate management infrastructure. This study found that violations of medical record confidentiality can be subject to criminal sanctions based on Statute 322 of the KUHP dan administrative sanctions by MKDKI. In the digital era, medical rescord security is becoming an increasingly complex issue that requires adaptive regulations and strengthened security systems. Legal education for medical personnels and the development of technology to support medical record management are indispensable. This research contributes to identifying challenges and opportunities in the utilization of medical records as legal evidence and promoting the protection of patient rights.